Public Relations: Membangun Komunikasi Internal dalam Perusahaan - Yugih Setyanto; Paula T. Anggarina (Kanal: Jurnal Ilmu Komunikasi, 2017)
Public relations had a management function within the company. The process of public relations entirely refers to a managerial approach consisting of fact finding, planning, communications and evaluation. In addition, public relations also runs internal activities to build good communication between the parties involved in the company to create a conducive working atmosphere. Internal communication within the company becomes an important element in creating a good working climate especially in companies whose employees have diverse cultural and social backgrounds. This paper discussed public relations in support of internal communication in the company.